Design And Fabrication Of A Low-Cost Mixer For A Biogas Digester - Akshat Kumar, Pragna Nannapaneni, Madhumita Samad, Dr. Rajeev Kumar (International Journal of Advanced Science and Technology, 2020)
This research is aimed to produce the maximum yield of biogas from a biogas digester by designing a low cost and power efficient mixing equipment. This mixer is designed so as to achieve a homogeneous mixture of cow dung (organic waste) and water in the ratio of 1:1, so as to increase the yield of biogas from the digester. This can then be utilized for elimination of waste food, cow dung and organic wastes to obtain a clean and renewable source of energy with reduced cost and pollution for the welfare of the society. After studying the existing designs and different materials for fabrication, mild steel was chosen to fabricate the final design of mixer, with two blades crossing at 90 degrees from each other. Forces were calculated and the design was analyzed before fabrication processes were carried out. The mixer was powered with a reverse switch such that the blades can change direction in every half rotation for a more even mixing. The mixer was installed over a floating digester of capacity 25 liters using arrangements of fasteners and was tested. The results unveiled that the biogas yield is enhanced upon maintaining the optimum temperature suitable for the bacterial growth. The high yield of biogas at such low cost makes it readily available to people of rural areas as a fuel, to replace the existing non-renewable sources, thereby,  helping them even earn their living from it.